Creativity Practices in 21st Century Quranic Tilawah Learning Among Islamic Education Teachers - Jalil, Mohd Zabani; Ismail, Ashraf; Usman, Abur Hamdi (International Journal of Psychosocial Rehabilitation, 2020)
The Quranic tilawah is one of the subtopics in the subject of Islamic education in primary school. It comprises four compulsory areas to be mastered that are reading, memorising, understanding, and tajweed. Since the advent of 21st Century Learning (PAK-21), student-centered learning that is being a part of the elements in PAK-21, especially the creativity ingredient, has been emphasised. However, the element of creativity has prompted the challenges among Islamic Education Teacher (IET) to be included in the study of the Quranic tilawah. It calls for students to deal face-to-face with their teacher. As such, the researchers are keen to explore how well IET can incorporate the elements of creativity in the Quranic tilawah study session. This study is a field case study involving four IETS as the study participants from four different primary schools in the state of Malacca. The data of this study were obtained through the interview process, observation on Learning and Facilitation (L&F), and document analysis. The findings show that the four study participants were able to incorporate elements of creativity into their Quranic tilawah teaching. However, creativity can only be applied to learning activities. Among the activities organised were creative i-think maps, jigsaw puzzles, singing, drawing, colouring, and origami. Nevertheless, creative i-think mapping activities manifest the highest frequency in the study participants’ practice. Overall, the findings of this study are intended to serve as a guide to further the practice of IETs’ creativity in the teaching of the Quranic tilawah, which has been fundamental in attracting students’ attention and focus on the Quranic tilawah’s L&F especially in the current generation of alpha.